IMPLEMENTASI PERATURAN BUPATI WAY KANAN NOMOR 48 TAHUN 2018 TENTANG TUGAS POKOK DAN FUNGSI BAGIAN HUMAS DAN PROTOKOL SEKRETARIAT DAERAH KABUPATEN WAY KANAN - I YUDA KARISMA; Ade Iskandar (e-JKPP, 2020)
The problem in this study is: (1) how to implement regulation of bupati's right way number 48 year 2018 about main duty and function of public relations bureau and protocol of regional secretariat of the district way kanan. (2) what aspects inhibit the implementation of the regent rules right way number 48 year 2018 about the main task and function of public relations bureau and protocol of the district secretariat district way kanan. The method of research used is qualitative with a descriptive analysis method.  The use of this method is to describe the policy implementation of regulation of the bupati's way kanan number 48 year 2018 about the main task and function of public relations bureau and protocol of the district secretariat district right way, to examine qualitative, how all data are obtained directly from the informant in the field using interviews and document studies. The results showed that the implementation of the regent rules way kanan number 48 year 2018 about the main task and function of public relations bureau and protocol, has been running well, the leader already implemented the existing regulations by giving the task to employees according to their background and ability, although in their execution is not optimal, it is due to the human resources, which is relatively lacking. Then, the inhibitory aspects are, (1) there are employees who do not know exactly the basic tasks and functions, sometimes employees feel the basic tasks that are carried out not according to the part. (2) often the employee is employed not a principal task that should be implemented, so that the officer does not perform the job optimally. In the field of work management, there is still a contradiction between what has been programmed and that has been done, (3) the solid task given by the leadership so that often the overlap of task and authority is carried out employees, because employees often work beyond their supposed working hours.